High strength and bioactivity polyvinyl alcohol/collagen composite hydrogel with tannic acid as cross‐linker - Bai, Zhongxiang; Wang, Tianyou; Zheng, Xin; Huang, Yanping; Chen, Yining; Dan, Weihua (Polymer engineering and science, 2021)
Hydrogels have great potential applications in biomedical materials, but their applications in complex physiological environments are severely limited by their weak strength and biotoxicity. Generally, synthetic polymer hydrogels and natural polymer hydrogels have complementary advantages in terms of mechanical strength and biological activity. Herein, tannic acid (TA), a natural material, was introduced into the polyvinyl alcohol/collagen (PVA‐COL) double network to prepare a hydrogel (PVA‐COL‐TA) with good bioactivity and mechanical properties. The tensile strength of the composite hydrogel can reach up to 20 times that of the pure PVA hydrogel. And the hydrogel after swelling under physiological conditions also exhibits stable mechanical properties. The introduction of TA can reduce the degradation rate of COL, enabling it to continue to exert biological activity. in vitro cytocompatibility experiments showed that PVA‐COL‐TA hydrogel has good sustained biological activity and the potential for biomedical materials. TA was introduced into the PVA‐COL two‐component hydrogel to prepare PVA‐COL‐TA hydrogels with high strength and biological activity. The introduction of tannic acid has a dual effect. On the one hand, the hydrogen bonding of PVA and TA can be seen as a “permanent cross‐linking” and its guarantee the strength of the composite hydrogels have biodegradable medical applications. On the other hand, the hydrophobic interactions and hydrogen bonding between COL and TA ensured that the collagen network is not rapidly degraded and continues to exert its biological activity.